Does Evolocumab, as a PCSK9 Inhibitor, Ameliorate the Lipid Profile in Familial Hypercholesterolemia Patients? A Meta-Analysis of Randomized Controlled Trials - Seyyed Majid Eslami; Shekoufeh Nikfar; Maryam Ghasemi; Mohammad Abdollahi (Frontiers Media S.A., 2017)
Proprotein convertase subtilisin-kexin type 9 (PCSK9) is a member of regulatory serine proteases which is mostly expressed in liver. In the physiological condition, LDL-C binds to LDL receptors (LDLRs) and via endocytosis, LDLRs are degraded. PCSK9 binds to the epidermal growth factor-like repeat A (EGFA) domain of extracellular LDLRs, and then physiological recycling of LDLRs from surface of liver is cancelled, resulting in elevation of circulating LDL-C in plasma. To evaluate whether evolucomab, as PCSK9 inhibitor monoclonal antibody, ameliorates lipid profile in familial hypercholesterolemia (FH) patients, this meta-analysis has been conducted. PubMed, Web of Science (ISI) and Scopus databases were searched for studies which had investigated the efficacy of evolucomab. Types of outcome investigated were percentage changes from baseline of the lipid profile. Our meta-analysis shows that evolucomab at the dosage of 420 mg monthly could decrease LDL-C  by 54.71%, TC by 35.08%, VLDL-C by 28.37 %, ratio of TC to HDL-C by 39.14 %, triglycerides by 12.11 %, and increased HDL-C by 6.06% from baseline compared to placebo at the end of study in FH patients. Our findings indicate that evolocumab could be a hopeful agent for challenging patients, such as statin intolerance or patients who fail to attain the target goal of LDL-C despite consumption of maximum doses of statins.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.